Unlearning learned helplessness by volunteerism and service-learning at the Iraq American University - Lynn Rose, M. (Opción, 2019)
As our research topic, we investigate ways in which gender equity can be improved in the educational setting, at all levels via comparative qualitative research methods. Specifically, we look at educational delivery in terms of learned helplessness. As a result, the early stages of learning are important to avoiding learned helplessness, but the principles of inclusivity are beneficial at any stage of education. In conclusion, Service Learning, especially those projects designed with community action in mind, is the centerpiece of our struggle to break the cycle of learned helplessness.